Electro-responsive shape memory hybrids - Tey, Yi Long (Nanyang Technological University, 2023)
This project aims to create an electro-activated shape memory material. The project successfully demonstrated a shape memory effect stimulate by electricity. The experiment result was repeatable many times and fully reversible within the elastic deformation region of the material.